2022
DOI: 10.3347/kjp.2022.60.5.309
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Extracellular Vesicles from Giardia lamblia Alleviates Dextran Sulfate Sodium-Induced Colitis in C57BL/6 Mice

Abstract: Inflammatory bowel disease (IBD) is a chronic and recurrent illness of the gastrointestinal tract. Treatment of IBD traditionally involves the use of aminosalicylic acid and steroids, while these drugs has been associated with untoward effects and refractoriness. The absence of effective treatment regimen against IBD has led to the exploration of new targets. Parasites are promising as an alternative therapy for IBD. Recent studies have highlighted the use of parasite-derived substances, such as excretory secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The production of EVs by G. intestinalis and the role of Giardia EVs in the parasite-host interaction has been described. Kim et al (2022) [ 11 ] showed that Giardia EVs improve clinical signs and reduce colon shortening in dextran sulfate (DSS)-induced colitis. The authors also observed that treatment with Giardia EVs suppressed neutrophil infiltration into colonic tissues, reducing inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The production of EVs by G. intestinalis and the role of Giardia EVs in the parasite-host interaction has been described. Kim et al (2022) [ 11 ] showed that Giardia EVs improve clinical signs and reduce colon shortening in dextran sulfate (DSS)-induced colitis. The authors also observed that treatment with Giardia EVs suppressed neutrophil infiltration into colonic tissues, reducing inflammation.…”
Section: Introductionmentioning
confidence: 99%